Integrating advanced computer-aided design, manufacturing, and numerical control principles and implementations - Xu, Xun, 1959- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
This book presents basic principles of product modeling and manufacturing while featuring contemporary industrial case studies. A one-stop reference source for the latest international standards, and their implementations, this comprehensive title also expands beyond the traditional scope of the product development process to give a brief account on product data management (PDM) and product lifecycle management (PLM).